Buckling of launch-vehicle cylinders under axial compression: A comparison of experimental and numerical knockdown factors. (October 2020) - Wagner, H.N.R.; Hühne, C.; Niemann, S.
Abstract: Metallic grid stiffened cylinders are often used as tank and interstage structures in launch-vehicle systems. When subjected to axial compression, these thin-walled shells are prone to buckling. The corresponding critical buckling load heavily depends on deviations from the ideal shell shape. In general, these deviations are defined as geometric imperfections and they can significantly reduce the critical load. Considering the influence of geometric imperfections into the design process of thin-walled shells poses major challenges for structural design. This article presents an overview regarding the modelling, analysis and design of metallic grid stiffened launch-vehicle cylinders. In comparison to commonly studied unstiffened cylinders, complex shells applied in aerospace engineering can have a completely different structural response to axial compression than their unstiffened counterparts. Advanced shell buckling design conceps like perturbation approaches and energy barrier criteria are applied and validated with experimental data. Finite element models are presented and described in detail. Important aspects like skin and weld buckling as well as the influence of cutouts are analyzed and discussed. Highlights: Imperfection sensitivity analysis of metallic launch-vehicle cylinders presented. Detailed studies regarding global, skin and weld buckling presented. Influence of multiple cutouts on the buckling load studied. Improved design criteria for orthogrid stiffened cylinder under axial compression presented and validated. Design analysis of the ULPM ITS of the Ariane 6 presented.